2002
DOI: 10.1093/jexbot/53.366.103
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitric oxide (NO) production by plant nitrate reductase in vivo and in vitro

Abstract: NO (nitric oxide) production from sunflower plants (Helianthus annuus L.), detached spinach leaves (Spinacia oleracea L.), desalted spinach leaf extracts or commercial maize (Zea mays L.) leaf nitrate reductase (NR, EC 1.6.6.1) was continuously followed as NO emission into the gas phase by chemiluminescence detection, and its response to post-translational NR modulation was examined in vitro and in vivo. NR (purified or in crude extracts) in vitro produced NO at saturating NADH and nitrite concentrations at ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
382
4
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 674 publications
(431 citation statements)
references
References 38 publications
13
382
4
10
Order By: Relevance
“…Nitrite is mutagenic and accumulation of NO 2 -may be detrimental to the plant in the long run. Furthermore, NR reduces not only NO 3 -to NO 2 - (Ruoff and Lillo 1990), but under certain conditions reduces also O 2 to form O 2 -(superoxide anion) and NO 2 -to form NO (nitric oxide) (Yamasaki 2000, Rockel et al 2002. Nitric oxide may have both detrimental and beneficial effects in plants, and the subject is far from fully understood.…”
Section: Toxic Products and By-products Of Nr: Nitrite Peroxynitritementioning
confidence: 99%
“…Nitrite is mutagenic and accumulation of NO 2 -may be detrimental to the plant in the long run. Furthermore, NR reduces not only NO 3 -to NO 2 - (Ruoff and Lillo 1990), but under certain conditions reduces also O 2 to form O 2 -(superoxide anion) and NO 2 -to form NO (nitric oxide) (Yamasaki 2000, Rockel et al 2002. Nitric oxide may have both detrimental and beneficial effects in plants, and the subject is far from fully understood.…”
Section: Toxic Products and By-products Of Nr: Nitrite Peroxynitritementioning
confidence: 99%
“…NR produces NO from nitrite by NAD(P)H-dependent manner. [21][22][23] Therefore, our previous study cannot rule out the side-effect of NO generated by the N assimilation. NO is involved in photoperiod and autonomous flowering pathway (NO represses the amplitudes of output pathway components CO and GI).…”
Section: Conservation Of Ampk-cry1 Pathway In Nutritional Signalingmentioning
confidence: 87%
“…Our later work showed that NO mediated by NR did not participate in defense response induced by COS, indicating that NO synthesized by NR may not act as a second messenger but have other functions. It had reported that NR might be responsible for the basal level of NO production in the leaves and roots of several plant species (Rockel et al 2002;Vanin et al 2004). Our previous work found a novel Ser/Thr protein kinase gene OIPK.…”
Section: Discussionmentioning
confidence: 99%